The Dirac equation in an external electromagnetic field: symmetry algebra and exact integration; Journal of Physics: Conference Series; Vol. 670, conf. 1 : XXIII International Conference on Integrable Systems and Quantum Symmetries (ISQS-23) - Breev A. I. Aleksandr Igorevich (2016, 2016)
Title screen